The effect of Chamomile Tea on Oral Mucositis among patients Undergoing Chemotherapy: Randomized Control Trail (Journal of Forensic Medicine & Toxicology, 2025)
Background: The side effect oral mucositis from chemotherapy harms patients who receive high-dose treatment because  it affects 9 out of 10 individuals. The current oral medication palifermin needs extra funding to treat patients especially  in less developed healthcare settings.Aim of study: This study aimed to test if chamomile tea can lower the harm oral  mucositis causes from chemotherapy.Material and Method: Babylon oncology center in Iraq ran an official experiment  with 75 patients split into two groups during medicinal studies. Card method was used to assign patients randomly into  different groups. During two weeks’ participants in the chamomile group needed to apply chamomile tea rinses to their  mouths three times a day but only standard medical care applied to the control group. WHO Mucositis Scale was used  to measure oral mucositis severity in patients both at the start, day 7, and day 14.Results: The chamomile treatment sig nificantly reduced oral mucositis pain for patients but worsened symptoms for control patients (p < 0.001). Out of the 20  participants, 75% had no more mucositis by day 14. oral mucositis severity related closely to cancer stage, length of chemotherapy treatment and patient oral hygiene practices as tested with p values under 0.05. Standard oral care protocols  for chemotherapy patients should include chamomile tea integration particularly in resource-limited healthcare facilities  because it effectively decreases OM severity
Keywords: Chamomile tea; Oral mucositis; Chemotherapy